Overview of the 2022 WHO Classification of Parathyroid Tumors - Erickson, Lori A.; Mete, Ozgur; Juhlin, C. Christofer; Perren, Aurel; Gill, Anthony J. (Endocrine pathology, 2022)
The 2022 WHO classification reflects increases in the knowledge of the underlying pathogenesis of parathyroid disease. In addition to the classic characteristic features of parathyroid neoplasms, subtleties in histologic features which may indicate an underlying genetic abnormality reflect increased understanding of the clinical manifestations, histologic, and genetic correlation in parathyroid disease. The importance of underlying genetic aberrancies is emphasized due to their significance to the care of the patient. Traditionally, the term “parathyroid hyperplasia” has been applied to multiglandular parathyroid disease; however, the concept of hyperplasia is generally no longer supported in the context of primary hyperparathyroidism since affected glands are usually composed of multiple “clonal” neoplastic proliferations. In light of these findings and management implications for patient care, the 2022 WHO classification endorses primary hyperparathyroidism-related multiglandular parathyroid disease (multiglandular multiple parathyroid adenomas) as a germline susceptibility-driven multiglandular parathyroid neoplasia. From such a perspective, pathologists can provide additional value to genetic triaging by recognizing morphological and immunohistochemical harbingers of MEN1 , CDKN1B , MAX , and CDC73 -related manifestations. In the current WHO classification, the term “parathyroid hyperplasia” is now used primarily in the setting of secondary hyperplasia which is most often caused by chronic renal failure. In addition to expansion in the histological features, including those that may be suggestive of an underlying genetic abnormality, there are additional nomenclature changes in the 2022 WHO classification reflecting increased understanding of the underlying pathogenesis of parathyroid disease. The new classification no longer endorses the use of “atypical parathyroid adenoma”. This entity is now being replaced with the term of “atypical parathyroid tumor” to reflect a parathyroid neoplasm of uncertain malignant potential. The differential diagnoses of atypical parathyroid tumor are discussed along with the details of worrisome clinical and laboratory findings, and also features that define atypical histological and immunohistochemical findings to qualify for this diagnosis. The histological definition of parathyroid carcinoma still requires one of the following findings: (i) angioinvasion (vascular invasion) characterized by tumor invading through a vessel wall and associated thrombus, or intravascular tumor cells admixed with thrombus, (ii) lymphatic invasion, (iii) perineural (intraneural) invasion, (iv) local malignant invasion into adjacent anatomic structures, or (v) histologically/cytologically documented metastatic disease. In parathyroid carcinomas, the documentation of mitotic activity (e.g., mitoses per 10mm 2 ) and Ki67 labeling index is recommended. Furthermore, the importance of complete submission of parathyroidectomy specimens for microscopic examination, and the crucial role of multiple levels along with ancillary biomarkers have expanded the diagnostic workup of atypical parathyroid tumors and parathyroid carcinoma to ensure accurate characterization of parathyroid neoplasms. The concept of parafibromin deficiency has been expanded upon and term “parafibromin deficient parathyroid neoplasm” is applied to a parathyroid neoplasm showing complete absence of nuclear parafibromin immunoreactivity. Nucleolar loss is considered as abnormal finding that requires further molecular testing to confirm its biological significance. The 2022 WHO classification emphasizes the role of molecular immunohistochemistry in parathyroid disease. By adopting a question–answer framework, this review highlights advances in knowledge of histological features, ancillary studies, and associated genetic findings that increase the understanding of the underlying pathogenesis of parathyroid disease that are now reflected in the updated classification and new entities in the 2022 WHO classification.